Smart Notification System on Medicine Dispenser - Nurhannani Iwani Hani Ekmal; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2025)
The principal objective of this project is to develop an intelligent medicine dispenser which has the capacity to automatically remind and supply medicine to the right person at the right time. It is useful to individuals who forget and make delays in taking their medication. This may cause severe health issues due to a lack of doses or the usage of the wrong type of medicine. The dispensing machine is placed on a NodeMCU ESP32 microcontroller. It is programmed in such a way that it dispenses medicine and reminds patients whenever they need to take it. In case the patient fails to consume the medicine, the system may be updated to notify of skipped doses. This intelligent system will make it easier for the patient to adhere to the medication schedule and be less dependent on family or caregivers’ assistance. It is also equipped with Wi-Fi, which offers mobile notifications and remote viewing, giving it the convenience, stability, and simplicity.